A prospective cohort study of novel functional types of parathyroid glands in thyroidectomy: In situ preservation or auto-transplantation?. Issue 52 (December 2016) - Cui, Qiuxia; Li, Zhihua; Kong, Deguang; Wang, Kun; Wu, Gaosong
Abstract : Abstract: The best method of preventing hypoparathyroidism after thyroidectomy is to keep parathyroid glands in situ. However, hypoparathyroidism still regularly occurs with the existing parathyroid classification system, and the incidence of permanent hypoparathyroidism has not been reduced. We created a novel system for classifying parathyroid glands that can guide parathyroid preservation in thyroidectomy. We prospectively observed parathyroid glands using the new system in 218 neck surgeries, compared with 132 under the traditional system from January 2014 to September 2015 at a single clinic center. Briefly, we classified parathyroid glands as follows: Type A, no dependency on the thyroid; B1, partial blood supply from the thyroid but retains adequate blood supply after removal of the thyroid; B2, partial blood supply from the thyroid and becomes devascularized after the removal of the thyroid; B3, blood supply mostly from the thyroid; and C, blood supply completely dependent on the thyroid. The classifications were used to decide between in situ preservation or auto-transplantation. The most common type of parathyroid gland was type B1 (53.77%), followed by type A (20.89%), which are the perfect categories for in situ preservation. Type B2 (17.52%) and type B3 (1.21%) have a chance to be kept in situ. For type C (6.61%), in situ preservation is impossible. When in-situ preservation is ruled out, parathyroid auto-transplantation is an alternative, with partial or total gland tissue, depending on the classification and the surgeon's discretion. Among the patients who were classified under the new system, 43.6% presented with transient hypoparathyroidism (symptoms lasting ⩽6 months) after surgery, versus 42.4% in the old system, which was not a significant difference. However, permanent hypothyroidism (symptoms lasting >6 months) was not detected in the applied group, but in 3.0% of patients in the nonapplied group ( P = 0.01). Our novel functional nomenclature system for parathyroid glands can provide a guide for preserving parathyroid function. For certain types, such as type B2 and C, instead of being kept in situ, auto-transplantation of partial or total parathyroid tissue is a prudent choice to ensure continued function.